Nitric oxide decreases stability of mRNAs encoding soluble guanylate cyclase subunits in rat pulmonary artery smooth muscle cells. - Filippov, G (1997)
Nitric oxide stimulates soluble guanylate cyclase (sGC) to convert GTP to the intracellular second messenger cGMP. In rat pulmonary artery smooth muscle cells, sGC is an obligate heterodimer composed of alpha1 and beta1 subunits. We investigated the effect of NO donor compounds on sGC subunit gene expression in rat pulmonary artery smooth muscle cells. Sodium nitroprusside and S-nitroso-glutathione decreased sGC subunit mRNA and protein levels, as well as sGC enzyme activity. 1H-[1,2,4]oxadiazolo[4,3-a]quinoxalin-1-one, an sGC inhibitor, blocked the effect of sodium nitroprusside on sGC subunit gene expression, whereas 8-bromo cGMP decreased subunit mRNA levels, demonstrating that NO-mediated decrease in sGC subunit mRNA levels is cGMP-dependent. sGC subunit mRNA levels decreased more rapidly in rat pulmonary artery smooth muscle cells exposed to NO than in cells exposed to actinomycin D, suggesting that NO decreases sGC subunit mRNA stability. Actinomycin D and cycloheximide blocked the ability of NO to decrease sGC subunit mRNA levels. These results demonstrate that NO decreases sGC subunit mRNA stability via a transcription- and translation-dependent mechanism.